THE OTTOMANS AND WESTERN EUROPEANS DURING THE MERCANTILIST TIMES: NEUTRALITY, COMPETITION AND CONFLICT - Bulut, Mehmet (Journal of Al-Tamaddun, 2020)
This paper seeks to explore the fundamental objectives and differences between the economic outlooks and policies of the Ottomans and western capitalist nations in the early modern period. As western European powers expanded their commercial trade worldwide, the Ottoman Empire simultaneously extended its influence east and west. However, the objectives, priorities and policies shaping both expansions were strikingly different. The Ottomans encouraged diverse commercial activities and traded with both Muslim and non-Muslim merchants within and beyond the Empire, who only needed to comply to several capitulations enforced by Ottoman authorities but were otherwise fully encouraged to enter the Ottoman market. The principal European mercantile communities were predominantly Dutch, British and French, and were not differentiated by political and economic policies. Their economic activities were rather supportive of the Ottoman economic priorities. However, the serious competition and consequently conflicts increased among western mercantilist nations in their commercial and economic activities in the territories of the Empire. This paper concludes that while Ottoman trade activities largely focused largely on human welfare, western mercantilists instead concentrated on profitability with the aim of â€œhomo-economicusâ€.